Soil erosion assessment in Tasik Chini Catchment using remote sensing and gis techniques - Muhammad Rendana; Sahibin Abdul Rahim; Wan Mohd Razi Idris; Tukimat Lihan; Zulfahmi Ali Rahman (Penerbit Universiti Kebangsaan Malaysia, 2017)
Over many years, forested land transformation into urban, agriculture and mining areas within Tasik Chini Catchment become more intense. These activities have negatively affected the catchment through soil erosion and increased the amount of sediments that deposited into the lake. Hence, the present study aimed to estimate soil erosion risk within Tasik Chini Catchment integrating the Revised Universal Soil Loss Equation (RUSLE) model and remotely sensed geospatial data. The multispectral imagery from LANDSAT 8 was used to provide up to date information on land cover within the catchment. The result shows the majority of Tasik Chini Catchment is classified at very low class (< 10 ton ha−1 yr−1) about 4835.34 ha (92.38%), followed by the low class (10-50 ton ha−1 yr−1) with total area of 175.47 ha (3.35%), moderate high class (50-100 ton ha−1 yr−1) with total area of 65.11 ha (1.24%), high class (100-150 ton ha−1 yr−1) with total area of 38.37 ha (0.73%) and very high class (> 150 ton ha−1 yr−1) with total area of 120.04 ha (2.30%). Tasik Chini Catchment is very susceptible to soil erosion especially on northwest and southeast regions, where the main sources of soil loss come from the agricultural, new settlements and mining activities. To conclude, the estimation of soil erosion model using remotely sensed data can be used to build sustainable development strategy within Tasik Chini Catchment in the future.